Health Care Seeking Behavior Among Rural Population of Thailand: Case Study in Ko-Hong District - Tansakul, Kanlaya (2010)
The purpose of this study is to ascertain the health status, self-care activities and patterns of access to care of the Universal Health Card (UC) insurance among the rural patients of Ko-hong sub-district in Southern Thailand and comparing it to the older, national health program, that is the Social Security Card (SSC) insurance. The design of the study involved triangulation of data from a survey (n = 396) with data from semi-structured interviews (n=10) and records from the Out Patient Department (OPD) card to check the actual health status in a smaller sample (n=10) of patients from rural Ko-hong sub-district. A random sample of 10 respondents provided the data via semi-structured interview of eight open-ended questions to seek the person’s definitions of health, besides assessing the respondents’ health status from OPD card, identifications of self-care strategies they used to maintain or promote their health, their views of the healthcare services they utilize, and how they think that being a person affect their health. Data from the survey (n = 396) found significant differences among the Ko-hong rural respondents by type of health insurance they used. When comparing the UC and the SSC respondents, the UC respondents had lower educational attainment, lower health status and were more likely among the low income live group in Ko-Hong rural area. The UC respondents reported undertaking a wide range of self-care activities for minor health problems, and rarely needing or seeking medical care for themselves. Health disparities between the UC and the SSC were also identified.